The Role of Students’ Intuition in Solving Basic Mathematical Problems in Mathematics Department of Education Faculty of Muhammadiyah Cirebon University - Arwanto Arwanto; I Ketut Budayasa; Mega Teguh Budiarto (Pancaran Pendidikan, 2018)
This study was conducted using qualitative approach, which aims to determine the role of students’ intuition in solving basic mathematical problems. Polya problem-solving steps was used for data collection followed by in-depth interview towards the subject of the study. The interview was conducted to know whether the subjects solve the problems intuitively or not. The subjects of the study are the first semester male students of Muhammadiyah Cirebon University. The result of this study indicates the role of mathematics student intuition in solving basic mathematics problems as follows: (1) In the process of learning basic mathematical problems, the subjects learn some basic mathematical problems intuititively. (2) In making problem-solving plans, subjects tend to use the role of direct intuition. (3) In making plans and applying mathematical problem, the subjects solve some problems without the role of intuition.